High‐performance tin‐oxide supercapacitors using hydrazine functionalising assisted by hydrogen plasma treatment. (23rd October 2019) - Abdollahi, Hassan; Samkan, Mahmoud; Mohajerzadeh, Mohammad Ala; Sanaee, Zeinab; Mohajerzadeh, Shams
Abstract : For the first time, the effects of adding hydrazine solution to tin‐oxide sol–gel to be used as an electrode in high‐performance supercapacitors have been studied. The mixed solution has been spin‐coated on stainless steel foils as substrates followed by exposing to hydrogen plasma treatment. The results show the effectiveness of adding hydrazine to tin‐oxide sol–gel, compared to pure tin‐oxide sol–gel. The electrochemical tests such as cyclic‐voltammetry and charge–discharge characteristics have been conducted, and the findings demonstrate the favourable contribution of adding hydrazine in increasing the capacitance of the supercapacitor. The physical properties of the tin‐oxide material have been analysed by means of FESEM, XRD, TEM, FT‐IR spectroscopy and Raman spectroscopy to have a better understanding of preparation procedure and better insight in material synthesis. The electrochemical tests demonstrate a high capacitance of 18 mF/cm 2 for the sample treated with hydrazine during the sol–gel processing which is around 40% higher than the merely prepared tin‐oxide sample. The measured values for the capacitance versus rate show a rather linear correlation between these parameters, further corroborating an electric‐double layer‐based performance for such devices.